The 2005 flood events in the Saskatchewan River Basin: Causes, assessment and damages. Issue 1 (2nd April 2016) - Shook, Kevin
Abstract : In June 2005, the headwater tributaries of the Saskatchewan River Basin in the western Canadian province of Alberta were struck by four heavy rain events. Runoff from the rainfalls resulted in three floods which extended from Alberta through the provinces of Saskatchewan and Manitoba, causing at least four deaths and property damages of CAD 400 million.